Charlie and the chocolate factory - Dahl, Roald; Hodge, Douglas (Puffin London, 2014)
Charlie longs to see inside Mr Willy Wonka's enormous chocolate factory. Now Mr Wonka, the most wondrous inventor in the world, has hidden golden tickets inside his delicious creamy chocolate bars. Only five winners can go through those great iron gates. Will one of them be Charlie?